POLIGAMI DALAM PANDANGAN MUHAMMAD SYAHRUR - Mushlihin Mushlihin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
The language approach performed by Syahrur in studying the al-Qur'an states that the legal product is very dependent on the socio-cultural context.Syahrur considers the need to reinterpret the texts of the Qur'an in the hope of synchronizing texts with the reality of society whenever and wherever. To realize his idea,Syahrur conceptualizes the Limit Theory (Nazoriyyat al-Hudud). With this Limit Theory,Syahrur tries to apply the texts of the muhkamat al-Qur'an into the reality of life with its limitations. The laws in the Qur'an according to him are elastic which can be drawn and adjusted to the context of place and time. The condition of the community is within the scope of the boundary, and as long as it does not exceed the prescribed limits, the law is permissible.Syahrur regarding polygamy which tries to attract a web of relations between the notion of text and reality deserves careful consideration and consideration.Syahrur wants to show that polygamy is a solution to social problems. Polygamy is considered as a means to provide protection for armalah (widows who have orphans). According to Syahrur, polygamy is an order of syara 'which aims to raise the dignity of single parent women.Syahrur thought about polygamy based on interpretations according to munasabah ayat and nazariya al-hudud (boundary theory),Syahrur does not adhere to the understanding of polygamy in a partial normative manner.